Circular and Transformative Economy Advances towards Sustainable Socio-economic Transformation - Nhamo, Luxon; Mpandeli, Sylvester; Liphadzi, Stanley; Mabhaudhi, Tafadzwanashe (Africa Circular Economy Series, 2024)
The main aim of this book is to illustrate circular models for sustainable resource management. It highlights the benefits of transformative approaches in integrating, simplifying, and facilitating understanding of complex systems and transforming systems towards greater sustainability while achieving multiple social, economic, and environmental outcomes. It provides pathways towards strategic policy decisions on socio-economic transformation supported by case studies. Features: Discusses exploration of a transitional path to the circular economy, explored from the point of view of waste and technology. Explains transformational change towards sustainable socio-ecological interactions. Reviews provision of pathways towards sustainability through scenario development. Provides assessment of progress towards Sustainable Development Goals. Presents cross-sectoral and multicentric approaches towards circularity. This book is aimed at researchers and professionals in water and environmental engineering, circular economy, sustainability, and environmental studies.